Assessment of Mothers’ Knowledge and Practices Concerning Cholera at Al-Muhandiseen Region in Hilla City - Talib M. Kudhair (Iraqi National Journal of Nursing Specialties, 2023)
Objective: To assess mothers' knowledge and practices concerning cholera and their relationship with somesociodemographic characteristics of those mothers.Methodology: A sample of (100) mother was selected through a convenience sample for the period of July Firstthrough August 31 2007 '؛. Data were collected through interview of mothers were visiting PHC centers by usingof constructed questionnaire developed by the researcher that contains (31) item. Reliability and Validity of thetool were determined through pilot study. A descriptive and inferential statistical approaches were used for dataanalysis.Results: The study indicated that mothers’ knowledge and practices concerning cholera were unacceptable andthere is a significant relationship between mothers’ knowledge and practices and some of theirsociodemographic characteristics such as age, level of education and economic status.Recommendations: The study recommended that an education program can be designed, constructed andimplemented to mothers about the disease and further and nation-wide studies can be conducted on a largesample size of mothers.